Konsep Tujuan Hidup Manusia: Tinjauan Teologis dalam Pendidikan Islam - Fatimah, Ima Frima; Ahmad EQ, Nurwadjah; Suhartini, Andewi (Jurnal Penelitian Pendidikan Islam, 2020)
This article aims to elaborate the concept of the purpose of human life as a theological foundation in Islamic education. Humans created by God have a number of predetermined goals. This research approach uses a qualitative approach with literature study methods. The results showed that there are two goals in human life that are closely related to their duties and functions as God's creatures, namely as a servant of God and as a caliph on the earth. The implication of two human goals on the process of Islamic education is how the education process forms a good servant of God and as a caliph on earth who has a responsible character, so as to realize a perfect human being.